Interactive fuzzy programming for two-level linear programming problems with random variable coefficients based on fractile criterion optimization model - Kato, K.; Jingtao Wang; Katagiri, H.; Sakawa, M. (2004 47th Midwest Symposium on Circuits and Systems, 2004)
In this paper, we focus on two-level linear programming problems involving random variable coefficients in objective functions and/or constraints. Using chance constrained programming techniques, the stochastic two-level linear programming problems are transformed into deterministic ones based on the fractile criterion optimization model. After introducing fuzzy goals for objective functions, interactive fuzzy programming to derive a satisfactory solution for decision makers is presented.